Implementation of General Principles of Good Governance (Aupb) in the Implementation of Regional Government - Muh. Arsul Haq Sulthan; Arwan Ridwan; Rudy Makanung (Masterpiece, 2026)
The implementation of the General Principles of Good Governance (Asas-Asas Umum Pemerintahan yang Baik—AUPB) constitutes a fundamental element of Indonesia's administrative law framework, ensuring that governmental authority is exercised lawfully, transparently, accountably, and in the public interest. This study examines the implementation of AUPB in regional governance and identifies the principal challenges affecting its effective application following the enactment of Law Number 30 of 2014 concerning Government Administration. The research adopts a normative legal research design employing statutory, conceptual, and case approaches. Secondary legal materials, including legislation, judicial decisions, scholarly books, and peer-reviewed journal articles, were systematically analyzed using qualitative descriptive and legal interpretation methods. The findings demonstrate that AUPB has strengthened the legal and ethical foundation of regional administrative decision-making by promoting legal certainty, impartiality, transparency, proportionality, accountability, and quality public services. Nevertheless, its implementation remains constrained by limited bureaucratic integrity, inconsistent institutional supervision, inadequate understanding of AUPB among public officials, political intervention in administrative processes, and the persistence of abuse of authority. These challenges hinder the realization of effective, citizen-oriented local governance. The study argues that optimizing AUPB implementation requires integrated institutional reforms, including strengthening internal and external oversight mechanisms, enhancing the professionalism and legal competence of civil servants, expanding electronic government systems, and enforcing administrative law consistently. These measures are essential to institutionalize good governance principles, improve public trust, and ensure sustainable, accountable, and responsive regional government administration in Indonesia.